Analisis Kesuksesan Sistem nformasi Manajemen Kepegawaian di Kejaksaan Negeri Purwakarta dengan Metode Delone dan Mclean - Devianti Anggraeni; Rangga Sanjaya (Neolectura, 2021)
Management information system is an information provider system that is used to support the operating system in the process of returning certain decisions within an institution/organization. The application of technology in government agencies is needed to create an accountable, transparent and trustworthy government. The personnel management information system is a useful application for managing administrative data, based on the Decree of the Attorney General of the Republic of Indonesia Number: KEP-155/J.A/12/1997 concerning the operational organization of the management information system of the Indonesian Attorney General's Office. This study aims to determine the success rate of the personnel management system at the Purwakarta District Attorney's Office using the Delone and McLean information system success model. The variables used in this research are system quality, information quality, service quality and user satisfaction. This research is a type of descriptive analysis research that is used to interpret the data that has been processed quantitatively. Based on the results of the study, there is a successful implementation of the Personnel Management Information System (SIMPEG) using the Delone and Mclean method, the quality of information has a positive and significant impact on user satisfaction of the Personnel Management System (SIMPEG), with a significance value of 0.007 <0.05 and a t value of 2,838 > t table 2,021.